STUDY ON ELECTRIC AND MAGNETIC PROPERTIES OF CNT(10,0) WITH SEMICONDUCTOR COMPOUNDS AND ATOM IMPURITIES - APRILIA (NIM: 20910013); Pembimbing: Dr.Suprijadi Haryono, ELY
Carbon nanotubes (CNTs) have been interesting research object since Ijima found it. Electronic and magnetic properties of CNT depend on its structure and chirality. Due to its exibility, CNT is expected as potential material for spintronic devices. Electronic property of CNT has been investigated by many researchers, in contrary with its magnetic properties especially in single walled CNT (10,0). In this thesis, we study on electric and magnetic for SWCNT (10,0) using density functional theory (DFT) and generalized gradient approximation (GGA) exchange correlation: The PHASE software was applied. Our systems are impurity in CNT surface with substitutional atoms. Different atom impurities were applied to study CNT impurities e.g. bismuth, gallium and arsenide atom as semiconductor based atom and also semiconductor alloy of gallium nitrogen arsenide. The result shows that magnetic properties were found due to SWCNT(10,0) depend on its impurities. Electronic properties change is also found in our calculation, bismuth impurity affected SWCNT (10,0) band gap less than perfect SWCNT (10,0), however our focus study is the effect of atom impurity in magnetic properties of SWCNT. Discussion about density of states and charge density of each structure related to magnetic properties of SWCNT (10,0) also discussed in this report.